Peningkatan Motivasi Belajar Peserta Didik SMPN 1 Garut Dalam Pembelajaran IPS Melalui Through Guessing Games - Alni Dahlena; Eldi Mulyana (FKIP, Universitas Palangka Raya, 2022)
In the current situation, in the midst of the spread of the Covid-19 pandemic, which is one of the challenges for students, especially in the educational aspect and society in general in social activities. Where student must carry out the learning with the limitations of supporting technology and the understanding of students in using the learning technology. Apart from these challenges, especially in social studies learning which in considered by students as a subject that is less acttrative and less motivated to learn social studies. So that students tend to be less enthusiastic when participating in learning, especially in distance learning. The purpose of this study to describe social studies learning innovations for students based on fun educational games for students. This research method is a qualitative method using case study techniques directly on students and literature students. The results of this study are; (1) social studies learning strategies based on fun educational games releted to simple social studies materials, but packaged in interesting patterns for students so that they can increase students motivation and interest in learning, especially in social studies leraning; (2) Increasing the optimalization of students in understanding social studies materials with the concept of strengthening reflection in social studies learning, especially in the introduction of regions and cultures in Indonesia.